An Analysis of Phatic Expressions Using Greetings & Salutations In English - Hot Saut Halomoan (e-LinguaTera, 2022)
Phatics expressions are vital in our day- to-day interactions with the society. They are intended to create ties of union among the people who interact with each other in the form of minitalk. The aim of the study includes (1) the reasons why phatic expressions are important in English, (2) the way how the pathic expressions are classified, (3) what makes them different from interjections. The data used are the greetings and salutations commonly used in English by employing some references regarding phatic particles, words and phrases. This is a descriptive research approach by collecting secondary data, analysing and classified accurately. This is just a preliminary survey without deeply analysing the data. The writer describes the phatic expressions based on the observations and examples by Beare, Kenneth and Nordquist, Richard on thoughtco.com. The data show that the beginning of a conversation, letter, email, or another form of communication, a salutation is a polite greeting, an expression of goodwill, or other sign of recognition. Salutation terms are an important part of a conversation to tell the other that we feel friendly toward them, and they are maybe the start of a longer conversation. The writer found that the phatics expressions are in the form of particles, words and phrases phatically. Based on the analysis it is concluded that the phatic pressions are purposed at strengthening solidarity and ties of union while interjections convey emotion and they are emotive while the phatic expressions are content-free and context-based. Syntactically the phatic expressions can be positioned either in the beginning, in the middle or in the end of the sentences or utterances while the interjections are only put in the beginning.